Impact of Short Story on the listening skills of the first year tertiary students in Indonesia - Via Rahmawati; Ika Rakhmawati (STAIN Sultan Abdurrahman Kepulauan Riau, 2022)
This study examines the effectiveness of short stories as alternative genre to engage students in listening practice. By employing quantitative approach, pre-experimental design was chosen to test the effect of short stories audio toward listening skills improvement. The participants of the research are first year college students of English Department in an Indonesian university. The phases in garnering the data was started with pre-test, followed by a designed treatment, and ended up with post-test to assess the effect. The result indicates that students' scores have increased after the treatment. The calculation of data with SPSS by considering Wilcoxon Rank Test results that there is improvement which post-test scores are higher than pre-test ones, which is 53.70 > 80.87, and the significance is 0.000 < 0.05. It suggests that short story is significantly effective for engaging students in listening practice and it further positively gives impact on listening skills. Therefore, short story could be an alternative genre used in the classroom as it possibly enthralls students to engage in listening activity.